Clinical inertia to insulin initiation and intensification in the UK: A focused literature review. Issue 1 (February 2017) - Khunti, Kamlesh; Millar-Jones, David
Highlights: Timely achievement of glycaemic control is key to optimising clinical outcomes. Clinical inertia is most pronounced at the intensification with insulin stage. The NICE guidelines on type 2 diabetes do not explicitly address clinical inertia. Barriers to treatment intensification span patient, clinician and system levels. Clinical inertia can be tackled with increased education on therapeutic options. Abstract: Achieving tight glycaemic control early following the diagnosis of type 2 diabetes is key to optimising clinical outcomes, yet many patients and clinicians are reluctant to initiate and intensify insulin therapy. Reasons for this arise primarily from a lack of time, clinical expertise and patient understanding. However, meaningful progress can be achieved with self-management educational programmes soon after diagnosis. Clinician education and training, along with easy-to-use and well-tolerated therapies (for example, those carrying a low risk of hypoglycaemia and/or avoiding weight gain), may also increase the likelihood of patient adherence.